The Concept Empowerment In Economics as Instrumen Development People Economic Indonesia - Aida, sastri (Al-Hijrah: Journal of Islamic Economics And Banking, 2025)
This article aims to describe the concept of empowerment as an instrument of people's economic development in Indonesia, by conducting a comparative study of the thoughts of Ibn Khaldun and Mohammad Hatta. The main formulation of this article highlights three focuses, namely the Thoughts of Ibn Khaldun and Mohammad Hatta, the concept of empowerment in Islamic economics and the combination of the concept of empowerment with economic development (Ibn Khaldun-Mohammad Hatta). The research method used is qualitative descriptive analysis through library research studies involving studies of classical and contemporary literature using the Publish or Perish application . The findings of this study, first: Ibn Khaldun provides a view of the concept of ashabiyah, while Hatta provides an understanding of the concept of empowerment through people's economics. Second, the concept of empowerment in Islamic economics is with the principles of Ukhuwah, Ta'awun, al-adlu . Third, the concept of empowerment offered by the two shops includes, Economic Equality, People's Participation, Social Welfare, Integrated Economy by creating references to economic democracy and economic cooperatives to encourage inclusive and sustainable economic development in Indonesia.